Analisa Teori Life Cycle pada Rumah Tangga Nelayan di Propinsi Kepulauan Bangka Belitung - Aning Kesuma Putri; Desy Yuliana Dalimunthe; Julia Julia (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2019)
The purpose of this study was to look at the life cycle of fisherman households in the Bangka Belitung Islands Province, considering that fishermen are a distinctive feature of the profession in the archipelago, it is possible that fishermen households have a contribution to savings patterns in the Bangka Belitung Islands Province. This research was conducted with primary data, in the form of question and answer and giving questionnaires to fishermen, with a total of 420 samples, consisting of 210 fishermen aged 18-42 years and 210 fishermen aged 42-80 years. This study uses a multiple linear regression research tool. The results showed that the life cycle of fishermen aged 18-42 years was influenced by permanent income, temporary income, assets, and savings as much as 32.6 percent while the life cycle of fishermen aged 42-80 years had a very small effect of 1.6 percent.